Demobilization of class politics in Denmark: the Social Democrats’ group-based appeals 1961-2004 - Thau, Mads (Politica, 2017)
Working-class support for social democratic parties has declined in Denmark and Western Europe generally. What role have social democratic parties played in the class demobilization? While existing work has considered policy positions, this article focuses instead on the group-based appeals of the Social Democrats. Based on content analysis of six party programs between 1964 and 2015, I find that class appeals have largely been replaced by appeals targeting non-economic groups. Also, the appeals that do concern class-related groups increasingly target businesses at the expense of traditional constituencies like workers, tenants and pensioners. Results imply that party strategy matters for the decline of class politics but also suggest that scholars should adopt a group perspective in future work.